COVID 19 and Higher Education Institution Operation: Unpacking the Potential of Higher Education through Acceptance of Online Learning - Alberto Ndekwa (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
This paper focused on analyzing the acceptance of online learning for unpacking the potential of higher education during COVID 19 lock down. Quantitative data was collected using questionnaire to a total sample of 258 respondents of Ruaha Catholic University. Systematic Sampling was used to pick a sample of students and academic staff where questionnaire were used to collect data for statistical analysis. Documentary review was used to get data to support and interpret findings from surveyed questionnaire. Data analysis using SEM revealed that usefulness and easiness of technology tend to influence the acceptance of using online learning method among students and academic staff of higher education. The significance influence of usefulness is explained by the fact that online learning is compatible to higher education environment which offer virtual learning and offer class to the students all the time while the easiness was found to be significant by the fact that online technology is ease to learn, ease to use and ease to access in higher education institution. It is concluded that for higher education community to accept online learning the technology should offer perceived benefit in terms of compatibility, virtual class, class should be available all the time and the technology should be simple and affordable. Addition, it is concluded that the technology should be ease to use, learn and access by community of higher education institution for them to accept it. This study recommends that the education institutions should design and implement the online learning system which is compatible, ease to use, ease to learn, ease to access and simple and affordable for every member of institution to unpack the COVID 19 Crisis. On the other hand, this paper recommends that training should be conducted to higher education institution community in order to educate them and create the awareness of the usefulness and easiness of online learning for them to unpack the COVID 19 Crisis.